Development of Red and Ox Game for Android Mobile Phone as Learning Media for Balancing Redox Equations - Ryan Hendra Cahyadhi; Achmad Lutfi (JCER (Journal of Chemistry Education Research), 2021)
Aim of this study was to discover the egibility of Red and Ox Game for android mobile phone as learning media for Balancing Redox Equations. This game egibility based on 3 criteria among them are validity, practicalitym and effectiveness. This study using Research and Development methods which consist of 3 main step (early study, development and teoritical validity, and game test itself). Result of this game validity is 88,63% from 3 different validator. Practically result for this game based on students responses is 87,71% with 84% of it student completed the whole game level. And effectiveness from this game result that 96% of this class surpassed standard score and paired t-test showed that after using this game there is difference between pretest and posttest which mean that this game is effective. Based on those 3 criteria, this game is proper as learning media for Balancing Redox Equations.